198k views
4 votes
14x + 6 = 5x - 3 with solution

User Ul
by
5.1k points

1 Answer

4 votes

hey there

the answer is

14x + 6 = 5x + -3


6 + 14x = 5x + -5

6 + 14x = -3 + 5x


6 + 14x + -5x = -3 + 5x + -5x


Combine like terms: 14x + -5x = 9x

6 + 9x = -3 + 5x + -5x


Combine like terms: 5x + -5x = 0

6 + 9x = -3 + 0

6 + 9x = -3

6 + -6 + 9x = -3 + -6


Combine like terms: 6 + -6 = 0

0 + 9x = -3 + -6

9x = -3 + -6


Combine like terms: -3 + -6 = -9

9x = -9


Divide each side by '9'.

x = -1


Simplifying

x = -1

thank you

OFFICIALLYSAVAGE2003

User Tamela
by
4.7k points